EP1121 The clinical potential of FOXL2 c.402C>G mutation detection in circulating tumour DNA of patients with granulosa cell tumours. (1st November 2019) - Groeneweg, JW; Roze, JF; Monroe, GM; Paijens, ST; Nijman, HW; van Meurs, HS; Lonkhuijzen, LRCW. van; Piek, JMJ; Lok, CAR; Jonges, GN; Zweemer, RP
Abstract : Introduction/Background: Adult granulosa cell tumours (aGCT) are rare ovarian malignancies, molecularly characterized by a single somatic c.402C>G mutation in FOXL2 . Recurrent disease after initial surgical treatment occurs in 30–50% of patients. Serum markers are used for diagnosis and follow-up, but are not always accurate for GCT monitoring. The use of circulating tumour DNA (ctDNA) to monitor disease has been suggested in many cancer types. We aimed to assess the presence of FOXL2 mutant ctDNA in aGCT patients and perform an initial evaluation of its potential as a marker for disease activity. Methodology: In a national, multicenter GCT study, plasma samples (n=27) were prospectively collected from 7 patients with primary (n=1) or recurrent (n=6) aGCT harbouring the FOXL2 c.402C>G mutation. Circulating cell-free DNA was extracted and assessed for the FOXL2 mutation using droplet digital PCR. Identification of FOXL2 mutation positive ctDNA, defined as ≥ 3 mutant droplets, was correlated with clinical parameters. Results: The FOXL2 c.402C>G mutation was found in the plasma of 5 out of 7 aGCT patients (71%), with mutant ctDNA fractions ranging between 0.4% and 47.8%. The tumour load in two patients without FOXL2 mutant ctDNA was limited, while all aGCT patients with FOXL2 mutant ctDNA had multifocal recurrent disease. In all ctDNA positive patients, increasing FOXL2 mutant ctDNA levels were associated with disease progression or relapse defined by a rise in serum markers and/or CT scan findings. In 3 out of 4 ctDNA positive patients with plasma taken before and after treatment, the observed clinical response to therapy was accompanied by a marked decrease in FOXL2 mutant ctDNA fractions. Conclusion: FOXL2 c.402C>G mutant ctDNA can be detected in patients with aGCT. Our results suggest that this test may have clinical value in disease monitoring, particularly when standard biomarkers inaccurately reflect tumour burden. Further research in a larger cohort is currently ongoing. Disclosure: Nothing to disclose